Pengembangan Komik Digital Berbasis Literasi Sains Pada Materi Perubahan Lingkungan - Marwani, Apradina; Adlini, Miza Nina (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to develop a scientific literacy–based digital comic on environmental change material that is valid, practical, and effective. The research employed a Research and Development (R&D) approach using the 4D model (Define, Design, Develop, Disseminate). The research subjects were 24 senior high school students in Serdang Bedagai Regency. Data were collected through questionnaires, interviews, expert validation sheets, teacher and student response questionnaires, and scientific literacy skills tests. The data were analyzed using descriptive quantitative techniques and N-gain analysis. The results showed that the digital comic was highly valid, with a media expert validation score of 91.52% and a material expert validation score of 96.25%. The practicality test yielded scores of 82.5% from teachers and 90.16% from students, categorized as very practical. The effectiveness test produced an N-gain value of 0.82, which falls into the high and effective category. Thus, the developed scientific literacy–based digital comic was proven to be valid, practical, and effective in enhancing students’ scientific literacy. This medium contributes as an innovative contextual learning resource aligned with the Merdeka Curriculum.